2009
DOI: 10.1509/jimk.17.3.71
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Brands from Emerging Markets: Brand Image across Host and Home Countries

Abstract: Cultural brands embody a sum total of a group's cultural identity, including a surrounding myth, a tie to its cultural roots, and associations of its past and aspired future. The authors focus on two cultural brands from Mexico and analyze whether their brand images remain consistent when they cross the border into the United States. Data were collected from random samples drawn from Mexico City and the Latino community (of Mexican descent) in the Dallas–Fort Worth area. Respondents were asked to evaluate two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(43 citation statements)
references
References 60 publications
(103 reference statements)
1
40
1
1
Order By: Relevance
“…The fi nding that frequent shoppers cannot be equated as frequent buyers modifi es Chadha and Husband's (2006) statement that when Asian consumers purchase foreign luxury brands they are also purchasing product to interpret what ' Britain ' means ( Jaffe and Nebenzahl, 2001 ). This differs from the fi ndings of Guzman and Paswan (2009) on successful cultural brands in emerging markets, which suggested that consumers of a foreign culture will evaluate the two separately. Ko et al 's (2007, p. 651) cross-national research pointed out that it is sometimes desirable for international fashion companies to lean towards a standardised strategy that can ' target cross-national market segments as opposed to developing individual segmentation schemes for each country ' .…”
Section: So I Don ' T Buy Their Things Now ( Female Shopper Who Visicontrasting
confidence: 57%
See 1 more Smart Citation
“…The fi nding that frequent shoppers cannot be equated as frequent buyers modifi es Chadha and Husband's (2006) statement that when Asian consumers purchase foreign luxury brands they are also purchasing product to interpret what ' Britain ' means ( Jaffe and Nebenzahl, 2001 ). This differs from the fi ndings of Guzman and Paswan (2009) on successful cultural brands in emerging markets, which suggested that consumers of a foreign culture will evaluate the two separately. Ko et al 's (2007, p. 651) cross-national research pointed out that it is sometimes desirable for international fashion companies to lean towards a standardised strategy that can ' target cross-national market segments as opposed to developing individual segmentation schemes for each country ' .…”
Section: So I Don ' T Buy Their Things Now ( Female Shopper Who Visicontrasting
confidence: 57%
“…With the forging of the factors discussed above, certain commercial brands thus become cultural ones ( O ' Reilly, 2005 ;Guzman and Paswan, 2009 ). According 2007 ), and it has been used in previous luxury brand studies ( Moore and Birtwistle, 2004 ;Aiello et al , 2009 ;Reddy et al , 2009 ).…”
Section: Methodsmentioning
confidence: 99%
“…The global value chains of these brands were driven by the producer, characterised by matured technology with rapid delocalisation aimed at building capabilities. A study by Guzmán and Paswan (2009) also focused on internationalisation of two cultural brands from Mexico in an attempt to analyse if reputation and image of a brand remains consistent in a foreign market, using a brand personality scale. Their findings revealed an association between brand personality and cultural image.…”
Section: Brands From Emerging Marketsmentioning
confidence: 99%
“…Through eight propositions, conditionings that stimulate or suppress the adoption of corporate brand were identified: interests of multiple stakeholders; emphasis on corporate image by stakeholders in emerging markets; complexity of the market; marketing costs; differences between industrial and consumer products; company size; period of experience; and extension of international experience. Perception of the country of origin is also included (Đorđević, 2008;Guzmán & Paswan, 2009;Lim & O'Cass, 2001;Pharr, 2005). Pérez and del Bosque (2014) corroborate Ghauri et al (2011) and Xie and Boggs's (2006) arguments by stating that, compared to the attributes of services and products, organizational attributes of corporate brands are more durable and resistant to competitive pressures.…”
Section: Brand Value As Intangible Asset (Brand Equity)mentioning
confidence: 99%